Desenvolvimento de banhos ácidos na presença de poliálcoois para eletrodeposição de liga de Zn-Ni. Caracterização eletroanalítica do processo de deposição e caracterização química, física e morfológica dos filmes de Zn-Ni - Oliveira, Edcarlos Moreira de (2008)
Development of acid baths in the presence of polyalcohols to Zn-Ni alloy electrodeposition. Electroanalytical caracterization of deposition process and chemical, physical and morphogical caracterization of the Zn-Ni film. In this thesis was studied the effect of added sorbitol, mannitol and glycerol polyalcohols to Zn-Ni alloys elctrodeposition baths, to obtain alloys with contend of Ni between 10 wt % and 18 wt %, and compact and homogeneous electrodeposits. The results showed that the boric acid in the Zn-Ni baths favored Ni deposition (~ 5 wt % - ~ 19 wt %) when the deposition potential and current density became more negative, i.e., from - 1.26 V to -1.55 V and from -25 mA cm-2 to -50 mA cm-2, respectively. The sorbitol or mannitol did not favour significantly the deposition of Zn or Ni. The best deposits were obtained at -1.40 V, onto Pt, from ZnNi2 (0.22M NiSO4 + 0.33M NiCl2 + 0.55M ZnSO4 + 0.26M H3BO3) + 0.52 M mannitol bath and onto steel, at - 50 mA cm-2 from ZnNi1 (0.22M NiSO4 + 0.33M NiCl2 + 0.55M ZnSO4 + 0.13M H3BO3) + 0.39 M sorbitol bath. Zn-Ni alloys electrodeposited onto Pt or 1010 steel substrates, from baths without and with polyalcohols, were formed of four main phases: δ (Zn22Ni3), γ (Zn21Ni5), γ1 (Zn3Ni) and β (ZnNi). The highest current efficiency (CE), 90 %, was obtained from baths contend glycerol. However, the CE range was 82 % - 85 % from baths without polyalcohol or with sorbitol or mannitol. Finally, corrosion test showed that the alloy corrosion potentials (Ecorr) were between the Ecorr of Zn and the Ecorr of steel. Thus, these alloys can be used as sacrificial layers on 1010 steel, with corrosion rate more slow than the Zn electrodeposits.